ANALISA KESUKSESAN OTA (ONLINE TRAVEL AGENT) TIKET.COM MENGGUNAKAN MODEL DELONE AND MCLEAN (Studi pada Pembelian Tiket Konser K-Pop di Indonesia) - Dhika Amalia Sholeha; Muhammad Zaini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The growth of Korean Wave in Indonesia has been very significant since the beginning of the pandemic in 2020 and the interest in K-Pop music is one proof of the phenomenon of Korean Wave in Indonesia. The huge interest in K-Pop music has attracted the attention of promoters to hold K-Pop music concerts in Indonesia. One of the elements in holding a music concert is ticket sales, and promoters will choose to prioritize online ticket sales to facilitate sales. One of the online ticket sales platforms for K-pop music concerts in Indonesia is tiket.com. As an online ticket sales platform, tiket.com must consider the quality of their system. This study aims to determine the factors that influence the success of the tiket.com platform using the DeLone and McLean Model theory (2003). The research method used is quantitative. The sampling technique used is nonprobability sampling technique with a sample of 100 respondents from tiket.com platform users who have transacted K-pop concert tickets. Data analysis was carried out using the PLS-SEM approach with the SmartPLS tool. The results of this study indicate that there is a significant effect on system quality, information quality and service quality on user satisfaction and a significant effect of user satisfaction on net benefits.